Novel anticoagulants: new evidence for emerging drugs and their potential application in major lower limb surgery. - Nikolaou, Vassilios S; Harwood, Paul J; Karadimas, Efthimios J; Tan, Hiang Boon; Giannoudis, Peter V (Curr Vasc Pharmacol, 2011)
For decades, parenteral drugs, such as the low molecular weight heparins and unfractionated heparins or vitamin K antagonists, have been used as anticoagulants for prevention of venous thromboembolism following major lower limb surgery. However, these regiments have limitations that rendered the quest for new anticoagulants mandatory. Recently, research has been focused on the development of orally active small molecules that directly target thrombin or activated factor X (FXa). These regiments exhibit a number of characteristics that an "ideal" anticoagulant should possess. Currently, two agents, dabigatran etexilate and rivaroxaban, which inhibit thrombin and FXa, respectively have been approved in the European Union and Canada for venous thromboprophylaxis in patients undergoing elective hip- or knee-replacement surgery. Other agents are at an early or late stage of clinical evaluation. In this study, we summarize the current evidence for these new developed or under development drugs regarding their applications in the filed of lower limb orthopaedic surgery.
Keywords: Anticoagulants; Benzimidazoles; Clinical Trials as Topic; Dabigatran; Drugs, Investigational; Factor Xa Inhibitors; Humans; Lower Extremity; Morpholines; Orthopedic Procedures; Pyridines; Rivaroxaban; Thiophenes; Thrombin; Venous Thromboembolism